Respiratory Viral Outbreak in Dental Clinics - A Review - VABUSHANA, V.JAYA; N. P, MURALIDHARAN.; R. GAYATHRI (The journal of contemporary issues in business and government, 2020)
A respiratory viral outbreak is the outbreak of viral disease related to respiration and respiratory system. Respiratory viral diseases are classified into two types. They are upper respiratory viral diseases and lower respiratory viral diseases. Some of the common respiratory viruses include influenza virus, respiratory syncytial virus, parainfluenza virus, adenovirus, rhinovirus, human metapneumovirus. The route of entry of the virus is from the outer environment the microbe gets inside the host body and reaches the target cells and starts multiplying inside the target cells and then burst opens, the newly formed viruses are released into the bloodstream of the host and those new viruses get new target cells in the host body, till it reaches the particular amount virus, there will be no symptoms seen. And the dental clinics are considered the high-risk zones for the outbreak of viruses. The aim of the review was to create awareness among the dentist about the respiratory viruses and to be safe and prevent outbreaks in dental clinics. This is a review study setting, evaluating the respiratory viral outbreaks in dental clinics. Data for the study were collected from search engines like PUBMED, GOOGLE SCHOLAR, MeSH, Cochrane, Semantic scholar. A total number of 70 articles were selected. In this review, the viral disease outbreaks are limited to the respiratory system. With this we can conclude that the data obtained from the present study may be useful for practitioners to be safe, prevent outbreaks and easy diagnosis of diseases and give treatment after precautions and preventive measures for the viral disease are taken.